1982
DOI: 10.1128/jcm.15.1.175-177.1982
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic activities of Legionella pneumophila and Legionella-like organisms

Abstract: The API ZYM system was used to investigate enzymatic activities of Legionella pneumophila and other Legionella-like organisms. Leucine aminopeptidase, alkaline and acid phosphatase, butyrate and caprylate esterase, and phosphoamidase activities were consistently detected in all strains tested. No evidence of myristate lipase, trypsin, chymotrypsin, or glycosidase activity was found. Legionella pneumophila and Legionella-like organisms have emerged as significant respiratory pathogens in certain patient populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…All of the L. pneumophila strains consistently metabolized Tween 40, Tween 80, methylpyruvate, ,3-hydroxybutyrate, a.-ketobutyrate, ox-ketovalerate, alaninamide, L-alanine, L-glutamate, glycyl-L-glutamate, L-leucine, L-proline, L-serine, L-threonine, and urocanate ( Table 1). The ability to utilize Tween 40 and Tween 80 suggests that L. pneumophila possesses esterase activity similar to that reported by Muller (18) and Nolte et al (19), except that our data suggest that the strains we investigated are able to split esters of higher fatty acids, as indicated by the metabolism of Tween 40 and Tween 80. Interestingly, although urocanate is an intermediate in histidine metabolism, only one of the strains tested, the serogroup 5 strain (NCTC 11405), was able to metabolize histidine within the 24-h incubation period.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…All of the L. pneumophila strains consistently metabolized Tween 40, Tween 80, methylpyruvate, ,3-hydroxybutyrate, a.-ketobutyrate, ox-ketovalerate, alaninamide, L-alanine, L-glutamate, glycyl-L-glutamate, L-leucine, L-proline, L-serine, L-threonine, and urocanate ( Table 1). The ability to utilize Tween 40 and Tween 80 suggests that L. pneumophila possesses esterase activity similar to that reported by Muller (18) and Nolte et al (19), except that our data suggest that the strains we investigated are able to split esters of higher fatty acids, as indicated by the metabolism of Tween 40 and Tween 80. Interestingly, although urocanate is an intermediate in histidine metabolism, only one of the strains tested, the serogroup 5 strain (NCTC 11405), was able to metabolize histidine within the 24-h incubation period.…”
Section: Resultssupporting
confidence: 89%
“…Our results seem to support this, as we found no metabolism of a-ketoglutarate, although the other keto-acids in the panel were metabolized by almost all of the strains investigated. All the strains tested metabolized methylpyruvate and ,-hydroxybutyrate, and most metabolized Tween 40 and Tween 80, suggesting that they possesses esterase activity, as reported previously (18,19). However, this may not be due to specific esterase activity but may be due to protease activity (24).…”
Section: Discussionsupporting
confidence: 66%
“…has been accomplished by techniques such as fluorescent antibody, DNA probes, latex fixation and biochemical tests all requiring highly complex equipment and trained personnel (Steele et al 1990). The BIOLOG system and the APY ZYM system are based on biochemical profiles (Nolte et al 1982). However, theoretical comparison of the APY ZYM system and the BIOLOG system reveals that the latter has the advantage of having considerably more substrates and not being pH-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…These tests can take more than one week. The enzymatic APY ZYM system (Nolte et al 1982) is too limited and non-specific for laboratory identification. We studied the BIOLOG system which uses metabolic fingerprints as a possible time-saving tentative test to improve Legionella spp.…”
mentioning
confidence: 99%
“…Humble et al (6) reported the system useful for enzymatic characterization of bacteria, yielding enzyme profiles for both gram-positive and gram-negative bacteria. Since 1977, API ZYME enzyme test kits have been used successfully to characterize a wide range of microorganisms of clinical importance (1,8,10,11).…”
mentioning
confidence: 99%